REINTERPRETING ARTICLE 251 KUHD: CASE STUDY OF CONSTITUTIONAL COURT DECISION NO. 83/PUU-XXII/2024 - Didi Jubaidi (Jurnal Humaniora & Sosial Sains, 2025)
Article 251 of the Indonesian Commercial Code (KUHD) grants insurance companies the right to unilaterally annul insurance contracts if the insured party conceals or misrepresents relevant facts, even without malicious intent. While grounded in the doctrine of uberrimae fidei (utmost good faith), this provision raises concerns about legal certainty and the balance of contractual rights. In 2024, the Indonesian Constitutional Court issued Decision No. 83/PUU-XXII/2024, declaring Article 251 conditionally unconstitutional. The Court ruled that insurance contracts cannot be annulled solely by the insurer without mutual agreement or a judicial decision, emphasizing the protection of constitutional principles of fairness and justice. This decision reshapes the legal landscape by limiting insurers' unilateral power and strengthening procedural fairness. It also urges the Financial Services Authority (OJK) to update legal frameworks and annulment procedures, reinforcing the protection of policyholders' rights.